Post-incarceration outcomes of a comprehensive statewide correctional MOUD program: A retrospective cohort studyResearch in context - Rosemarie A. Martin; Nicole Alexander-Scott; Justin Berk; Ryan W. Carpenter; Augustine Kang; Ariel Hoadley; Eliana Kaplowitz; Linda Hurley; Josiah D. Rich; Jennifer G. Clarke (Elsevier, 2023)
Summary: Background: As opioid overdoses surge, medications for opioid use disorder (MOUD) remain underutilized. MOUD is rarely offered in correctional facilities although individuals involved in the criminal justice system have higher rates of OUD and mortality relative to the general population. Methods: A retrospective cohort design examined the effect of MOUD while incarcerated on 12 months post-release treatment engagement and retention, overdose mortality, and recidivism. Individuals (N = 1600) who participated in the Rhode Island Department of Corrections (RIDOC) MOUD program (the United States' first statewide program) and were released from incarceration from December 1, 2016, to December 31, 2018, were included. The sample was 72.6% Male (27.4% female) and 80.8% White (5.8% Black, 11.4% Hispanic, 2.0% another race). Findings: 56% were prescribed methadone, 43% buprenorphine, and 1% naltrexone. During incarceration, 61% were continued on MOUD from the community, 30% were inducted onto MOUD upon incarceration, and 9% were inducted pre-release. At 30 days and 12 months post-release, 73% and 86% of participants engaged in MOUD treatment, respectively, and those newly inducted had lower post-release engagement than those who continued from the community. Reincarceration rates (52%) were similar to the general RIDOC population. Twelve overdose deaths occurred during the 12-month follow-up, with only one overdose death during the first two weeks post-release. Interpretations: Implementing MOUD in correctional facilities, with seamless linkage to community care is a needed life-saving strategy. Funding: Rhode Island General Fund, the NIH of Health HEAL Initiative, the NIGMS, and the NIDA.